2023
DOI: 10.1039/d2ra07244k
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic chiral polymeric nanoparticles for asymmetric aldol reaction

Abstract: Chiral polymeric particles (CPPs) were studied extensively in recent years due to their importance in pharmaceutical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…This pivotal nding marked the emergence of a new era in organocatalysis, leading to extensive research over the past two decades on metal-free amino acid-based catalysis. [11][12][13][14][15][16][17][18][19] The signicant contributions of this eld to various scientic and technological domains were acknowledged through the 2021 Nobel Prize in Chemistry. In contrast, our previous study revealed limited browning reactivity of L-proline in acetone/DMSO, while L-tryptophan exhibited the highest browning potential within our specic system.…”
Section: Introductionmentioning
confidence: 99%
“…This pivotal nding marked the emergence of a new era in organocatalysis, leading to extensive research over the past two decades on metal-free amino acid-based catalysis. [11][12][13][14][15][16][17][18][19] The signicant contributions of this eld to various scientic and technological domains were acknowledged through the 2021 Nobel Prize in Chemistry. In contrast, our previous study revealed limited browning reactivity of L-proline in acetone/DMSO, while L-tryptophan exhibited the highest browning potential within our specic system.…”
Section: Introductionmentioning
confidence: 99%